Synthesis of silica-polymer core-shell nanoparticles by reversible addition-fragmentation chain transfer polymerization - Moraes, John; Ohno, Kohji; Maschmeyer, Thomas; Perrier, Sébastien (Chemical communications (Cambridge, England), 2013)
Hybrid nanoparticles hold great promise for a range of applications such as drug-delivery vectors or colloidal crystal self-assemblies. The challenge of preparing highly monodisperse particles for these applications has recently been overcome by using living radical polymerization techniques. In particular, the use of reversible addition-fragmentation chain transfer (RAFT), initiated from silica surfaces, yields well-defined particles from a range of precursor monomers resulting in nanoparticles of tailored sizes that are accessible via the rational selection of polymerization conditions. Furthermore, using RAFT allows post-polymerization modification to afford multifunctional, monodisperse, nanostructures under mild and non-stringent reaction conditions.